Christ Among Them Incarnation and Renaissance in Medieval Italian Culture. - Mungiello, Edoardo (Newcastle upon Tyne : Cambridge Scholars Publishing, 2008)
This essay newly interprets the rise of the individual Otherin the Italian peninsula between 1180 and 1300. It follows the historical events and the cultural products that define the period keeping in mind that the creators were conscious of a tangible, real Christ in their midst. For it is the time when Jesus was known to be in the Eucharist as a carnal potentiality, as well as a time when Europeans on Crusade had reached his temporal abode. As Christ as neighbor became a consistent idea, the...
Table of contents; acknowledgements; a brief note; preface; introduction; chapter one; chapter two; chapter three; chapter four; chapter five; chapter six; epilogue; bibliography; index
Description based upon print version of record.
Keywords: Incarnation -- History of doctrines -- Middle Ages, 600-1500.; Individualism -- Religious aspects -- Christianity; Italy -- Church history -- 476-1400.; Incarnation -- History of doctrines -- Middle Ages, 600-1500.; Individualism -- Religious aspects -- Christianity; Italy -- Church history -- 476-1400.; RELIGION / Christian Theology / Christology; Electronic books